Factors influencing farmer-to-farmer transfer of an improved cowpea variety in Kano State, Nigeria - Kormawa, P.M.; Ezedinma, C.I.; Singh, B. (2004)
Diffusion of improved technologies among small-scale farmers, especially where formal methods and market mechanisms are inefficient, can be enhanced through the participation of farmers. Unfortunately, formal methods of disseminating improved seed in most African countries have not taken advantage of the farmers’ traditional transfer methods. This article deals with the role of farmer-to-farmer transfer and dissemination of an improved cowpea seed variety in Nigeria. Using household and farm level data from 133 respondents, the study adopts a logit model to investigate the determinants of the farmers’ decision to transfer the new seed variety to other farmers.Area of improved cowpea cultivated, yield, market price of seed, use of pesticides and threshing quality were found to be significant variables affecting farmers’ decision to transfer the improved cowpea variety.